Investigating the Impact of Stimulus Equivalence on Children’s Food Choice and Preference - Santos,Silvana Lopes dos (2018)
Abstract This study investigated the influence of character on food's choices. Eleven preschool children were trained to form two equivalent stimulus classes, each comprising one a cartoon character, a geometric shape, and an abstract symbol. One class had a liked character and the other a disliked character. Three preference tests were conducted where the children had to choose between two identical packages with samples of the same snack, differing only by the label. In Test 1 the labels were symbols of the same class as the liked and disliked characters; in Test 2 the choice was between the symbol of the same class as the disliked character and a new symbol; and in Test 3 children chose between the symbol of the equivalence class with the liked character and the logo of a known brand. Most children chose first, and reported to like more, the snack labeled with the symbol of the same class as the liked character. They also chose, and reported to like more, the snack labeled with a new stimulus over the symbol of the same class as the disliked character. These results confirmed that stimulus equivalence is a useful paradigm to investigate formation of preference for brands.